Key environmental predictors as drivers of avifauna assemblages in Ghana’s coastal ecosystems - Samuel Etornam Tamekloe; Kweku Ansah-Monney; Justus Precious Deikumah (Discover Environment)
Abstract Avian assemblages are not only influenced by spatial factors but also by temporal variations in environmental conditions, creating dynamic patterns of bird presence in a given area. This study examined environmental elements affecting bird assemblages in Ghana's coastal ecosystems. We conducted point transect sampling along a 15-km coastal stretch, analyzing bird abundance, richness, and diversity in relation to microclimate and urbanization. Humidity and wind speed had a significant negative relationship with bird abundance as well as time of day (morning) having a negative relationship. Mean bird richness, diversity, were significantly higher in natural shoreline areas compared to urbanized ones. Bird abundance and seasonality were positive related where wet season was characterized by higher bird numbers which can be attributed to the favorability of the wet season in terms of food availability and habitat suitability. Indicator Species Analysis identified nineteen species significantly associated specific habitat characterization, with eleven species linked to lagoon adjacent shorelines. These results show the relationship between environmental factors and avian assemblages in coastal ecosystems, highlighting impacts of human disturbance and climate-related factors and the importance of pristine ecosystems in biodiversity conservation.